Negative electrode sheet, method for manufacturing the same, and solid-state lithium ion battery
Patent Information
- Application Number
- CN202611080871.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-21
AI Technical Summary
[0005]本发明提供了一种负极极片,以解决现有技术中电极稳定性较差、界面阻抗较高、电池首效和倍率较低、循环性能较差的问题
本发明提供的负极极片中交联剂、稳定功能单体、粘附功能单体在电极内部原位形成连续、高弹性的三维网络,实现硅活性材料在网络中分子尺度上的均匀分散,提高均一性,能够通过可逆的弹性形变有效吸收和缓冲硅颗粒在充放电过程中产生的巨大体积变化应力(>300%),避免了因反复膨胀收缩导致的活性物质粉化、电极涂层开裂以及活性物质与集流体间的物理剥离,从而极大幅度提升了电极的机械完整性与循环结构稳定性,因此含本发明负极极片的固态锂离子电池具有高倍率性能、高首次库伦效率和优秀的循环稳定性,且电池在低外力下(10MPa)也可以稳定运行。
Smart Images

Figure CN122599369B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a negative electrode sheet, its preparation method, and a solid-state lithium-ion battery. Background Technology
[0002] With the rapid development of industries such as electric vehicles and the low-altitude economy, the requirements for battery energy density and safety are constantly increasing. The energy density of traditional liquid lithium-ion batteries is gradually approaching its theoretical limit, and there are safety hazards such as leakage of organic electrolytes and flammability. All-solid-state batteries, which use non-flammable solid electrolytes instead of liquid electrolytes, are considered the core direction of next-generation high-safety, high-energy-density energy storage technology. Among them, sulfide solid electrolytes are particularly noteworthy due to their ultra-high ionic conductivity (reaching 10⁻⁶ at room temperature), comparable to liquid electrolytes. -2 S / cm-10 -3 With its excellent mechanical deformability and S / cm, it has become the most promising solid electrolyte system for industrialization.
[0003] The negative electrode of a lithium-ion battery is the core component of the battery. Currently, the widely used graphite negative electrode can hardly meet the requirements. In order to achieve higher energy density, using silicon negative electrode (the theoretical specific capacity of silicon is 3579 mAh / g, which is close to 10 times the specific capacity of graphite) to replace graphite negative electrode is an effective solution. Therefore, the development of a battery system of "sulfide solid electrolyte + silicon negative electrode" is regarded as the most critical technical route to achieve a high energy density of 400Wh / kg all-solid-state battery.
[0004] In sulfide all-solid-state batteries, the initial development of silicon anodes was similar to that of liquid batteries. This involved dispersing sulfide electrolytes (SSEs) and silicon anodes in a polar organic solvent, followed by a slurry coating process to obtain the silicon anode sheet. SSEs facilitate ion transport within the anode, but this electrode design has limitations. The main issue is the poor compatibility and stability of SSEs in common polar solvents (such as N-methylpyrrolidone and water), which easily leads to SSE decomposition. The process is complex and precise interface control is difficult. The optimal strategy is to omit the addition of SSEs during anode sheet preparation, using a polar solvent for slurry preparation. This results in a 2D interface between the silicon anode and the sulfide electrolyte membrane, mitigating electrolyte decomposition. However, this method fails to address a fundamental problem: the significant volume expansion of the silicon anode disrupts the integrity of the electrode structure, deteriorating the internal structure and the contact with the electrolyte membrane. Therefore, extremely high external pressures (>100 MPa) are typically required during battery testing to maintain physical contact, hindering practical application of the battery. Secondly, the narrow electrochemical stability window of sulfide electrolytes leads to continuous growth of the solid electrolyte interphase (SEI) film and the formation of pores at the interface between the two-dimensional silicon anode (2DSi) and the lithium phosphorus sulfur chloride solid electrolyte (LPSCI). This severely consumes active lithium and increases interfacial impedance, resulting in poor initial efficiency and cycle performance. Thirdly, because SSEs cannot penetrate into the silicon anode, the electrical contact failure caused by external volume changes makes it difficult to form a stable ion / electron percolation network in the silicon anode, resulting in a low battery rate. Summary of the Invention
[0005] This invention provides a negative electrode sheet to solve the problems of poor electrode stability, high interface impedance, low initial efficiency and rate capability, and poor cycle performance in the prior art.
[0006] In a first aspect, the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode slurry coated on at least one side of the current collector, wherein the raw materials of the negative electrode slurry include: silicon active material, lithium salt, initiator, crosslinking agent, stabilizing functional monomer, adhesion functional monomer and vanadate-polyaniline composite. The crosslinking agent contains an oxyethylene segment and two substituted or unsubstituted acryloyl groups; wherein the substituents of the substituted acryloyl groups include C1-C3 alkyl groups; The stabilizing functional monomer contains acrylates with 3-6 fluorine atoms substituted for alkyl groups; The adhesive functional monomer contains double bonds and carboxyl groups.
[0007] In one alternative embodiment, the crosslinking agent includes at least one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
[0008] In one optional embodiment, the stabilizing functional monomer comprises at least one selected from 2,2,2-trifluoroethyl acrylate, 2,2,2-trifluoroethyl methacrylate, hexafluorobutyl acrylate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, and 1,1,1,3,3,3-hexafluoroisopropyl acrylate. As an example, the stabilizing functional monomer may be 2,2,2-trifluoroethyl acrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, or 1,1,1,3,3,3-hexafluoroisopropyl acrylate.
[0009] In one optional embodiment, the adhesive functional monomer includes at least one selected from maleic acid, itaconic acid, citraconic acid, and acrylic acid. As an example, the adhesive functional monomer may be maleic acid, citraconic acid, or itaconic acid.
[0010] In one optional embodiment, the mass ratio of the crosslinking agent to the stable functional monomer is 1:(1-3). As an example, the mass ratio of the crosslinking agent to the stable functional monomer can be 1:1, 1:1.5, 1:2, 1:2.5, or 1:3.
[0011] In one optional embodiment, the molar ratio of the stabilizing functional monomer to the adhesive functional monomer is 1:(0.5-3). As an example, the molar ratio of the stabilizing functional monomer to the adhesive functional monomer can be 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, or 1:3.
[0012] In one optional embodiment, the initiator is 1 wt%-2 wt% of the total mass of the crosslinking agent, the stabilizing functional monomer, and the adhesive functional monomer. As an example, the initiator may be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, or 2 wt% of the total mass of the crosslinking agent, the stabilizing functional monomer, and the adhesive functional monomer.
[0013] In one optional embodiment, the lithium salt is calculated based on elemental lithium, and the crosslinking agent is calculated based on ethylene oxide segments (EO segments), with a molar ratio of ethylene oxide segments to elemental lithium of (16-20):1. As an example, the crosslinking agent, calculated based on ethylene oxide segments (EO segments), may have a molar ratio of ethylene oxide segments to elemental lithium of 16:1, 17:1, 18:1, 19:1, or 20:1.
[0014] In one optional embodiment, the total mass ratio of the crosslinking agent, the stabilizing functional monomer, and the adhesive functional monomer to the silicon active material and the vanadate-polyaniline composite is (0.5-1.5):8:(0.5-1.5). As an example, the mass ratio of the total mass of the crosslinking agent, the stabilizing functional monomer, and the adhesive functional monomer to the silicon active material and the vanadate-polyaniline composite can be 0.5:8:0.5, 0.5:8:1, 0.5:8:1.5, 1:8:0.5, 1:8:1, 1:8:1.5, 1.5:8:0.5, 1.5:8:1, or 1.5:8:1.5.
[0015] In one optional embodiment, the number-average molecular weight of the polyethylene glycol diacrylate is 3000-5000. As an example, the number-average molecular weight of the polyethylene glycol diacrylate can be 3000, 3500, 4000, 4500, or 5000.
[0016] In one optional embodiment, the number-average molecular weight of the polyethylene glycol dimethacrylate is 3000-5000. As an example, the number-average molecular weight of the polyethylene glycol dimethacrylate can be 3000, 3500, 4000, 4500, or 5000.
[0017] In one optional embodiment, the preparation method of the vanadate-polyaniline composite includes the following steps: reacting aniline with sulfuric acid solution to obtain mixed solution A; reacting ammonium decavanadate and an oxidant in deionized water to obtain mixed solution B; reacting mixed solution A with mixed solution B to obtain the vanadate-polyaniline composite; the pH value of mixed solution B is 2-3.
[0018] In one optional embodiment, the molar ratio of aniline to sulfuric acid is 1:(0.5-1.5). As an example, the molar ratio of aniline to sulfuric acid can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, or 1:1.5.
[0019] Further, the concentration of the sulfuric acid solution is 0.1 mol / L to 0.3 mol / L. As an example, the concentration of the aqueous sulfuric acid solution can be 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, or 0.3 mol / L.
[0020] In one alternative embodiment, the oxidant includes at least one of ammonium persulfate, potassium persulfate, and sodium persulfate.
[0021] It should be noted that, in this invention, ammonium decavanadate includes ammonium decavanadate hexahydrate.
[0022] In one optional embodiment, the mass ratio of aniline, ammonium decavanadate, and oxidant is 1:(0.5-2):(2-5). As an example, the mass ratio of aniline, ammonium decavanadate, and oxidant can be 1:0.5:2, 1:0.5:4, 1:1:3, 1:1:5, 1:2:5, or 1:2:2.
[0023] In one optional embodiment, the reaction temperature is room temperature, and the reaction time is 18-30 hours. For example, the reaction time can be 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, or 30 hours.
[0024] Further, the mixed solution A is added dropwise to the mixed solution B; optionally, the dropping rate is 3s / drop-5s / drop.
[0025] In one alternative embodiment, the lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethane)sulfonylimide. As an example, the lithium salt may be lithium bis(fluorosulfonyl)imide.
[0026] In one optional embodiment, the initiator includes at least one of azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile (AIH). As an example, the initiator may be AIBN.
[0027] In one optional embodiment, the silicon-active material includes at least one of micron-sized silicon, silicon-oxygen materials, and silicon-carbon materials. As an example, the silicon-active material may be micron-sized silicon.
[0028] In one optional embodiment, the particle size of the micron-sized silicon is 1 μm-5 μm. As an example, the particle size of the micron-sized silicon can be 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.
[0029] In a second aspect, the present invention provides a method for preparing the negative electrode sheet described in the first aspect, comprising the following steps: mixing the raw materials of the negative electrode slurry and reacting them to obtain the negative electrode slurry, coating it onto a current collector and heating it to obtain the negative electrode sheet.
[0030] In one optional embodiment, the heating step includes: first heating at 60℃-80℃ for 5h-15h, and then heating at 85℃-95℃ for 5h-15h.
[0031] In one alternative implementation, the heating step is performed under an inert atmosphere or a vacuum.
[0032] Thirdly, the present invention provides an application of the negative electrode prepared by the method described in the second aspect in a solid-state lithium-ion battery.
[0033] The technical solution of this invention has the following advantages: The negative electrode sheet provided by this invention forms a continuous, highly elastic three-dimensional network in situ inside the electrode by crosslinking agent, stabilizing functional monomer, and adhesion functional monomer. This achieves uniform dispersion of silicon active material at the molecular scale in the network, improving uniformity. It can effectively absorb and buffer the huge volume change stress (>300%) generated by silicon particles during charging and discharging through reversible elastic deformation, avoiding active material pulverization, electrode coating cracking, and physical peeling between active material and current collector caused by repeated expansion and contraction. This greatly improves the mechanical integrity and cycle structure stability of the electrode. Therefore, solid-state lithium-ion batteries containing the negative electrode sheet of this invention have high rate performance, high initial coulombic efficiency, and excellent cycle stability. Moreover, the battery can operate stably under low external force (10MPa). Attached Figure Description
[0034] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0035] Figure 1 This is a schematic diagram of the vanadate-polyaniline composite of the present invention; Figure 2 This is a cycle test diagram of the sulfide all-solid-state half-cell obtained in Example 1 of the present invention; Figure 3 This is the battery impedance diagram of the sulfide all-solid-state half-cell obtained in Example 1 of the present invention after 50 cycles; Figure 4 This is a peel strength diagram of the sulfide all-solid-state half-cell electrode obtained in Example 1 of the present invention. Detailed Implementation
[0036] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.
[0037] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0038] Polyethylene glycol diacrylate (PEG) was purchased from Merck Chemicals, model number 907227, with a number average molecular weight of 3000-5000; polyethylene glycol dimethacrylate (PEG) was purchased from Merck Chemicals, model number 437468, with a number average molecular weight of 3000-5000; the median particle size of the micron-sized silica was 1μm-5μm, and the tap density was 0.6 g / cm³. 3 -1.2g / cm 3 The carbon layer thickness is 10nm-20nm.
[0039] Preparation Example 1 This preparation example provides a method for preparing a vanadate-polyaniline composite, comprising the following steps: Aniline (0.93 g) was dissolved in 50 mL of 0.2 mol / L sulfuric acid aqueous solution and stirred until homogeneous to obtain solution A; ammonium vanadate hexahydrate (NH4)6V 10 O 28 ·6H₂O (1.0 g) and ammonium persulfate (3.42 g) were dissolved in deionized water (50 mL), and the pH was adjusted to 2-3 with dilute sulfuric acid (0.1 mol / L). The mixture was stirred until completely dissolved to obtain solution B. Under stirring conditions at room temperature (25 °C), solution A was added dropwise to solution B at a rate of 3-5 s / drop. After the addition was complete, the reaction was continued with stirring for 24 h. After the reaction was complete, the solid product was obtained by filtration, washed thoroughly with deionized water, and dried under vacuum at 80 °C for 24 h to obtain the final product.
[0040] Figure 1 This is a schematic diagram of the structure of the prepared vanadate-polyaniline composite. Figure 1 It can be seen that multilayered polyaniline (PANI) interlayers are embedded with ordered and protonated decavanadate clusters to form layered nanocomposite materials.
[0041] Preparation Example 2 This preparation example provides a method for preparing a vanadate-polyaniline composite, comprising the following steps: Aniline (0.93 g) was dissolved in 50 mL of 0.1 mol / L sulfuric acid aqueous solution and stirred until homogeneous to obtain solution A; ammonium vanadate hexahydrate (NH4)6V 10 O 28·6H₂O (0.465 g) and potassium persulfate (1.86 g) were dissolved in deionized water (50 mL), and the pH was adjusted to 2-3 with dilute sulfuric acid (0.1 mol / L). The mixture was stirred until completely dissolved to obtain solution B. Under stirring conditions at room temperature (25 °C), solution A was added dropwise to solution B at a rate of 3-5 s / drop. After the addition was complete, the reaction was continued with stirring for 18 h. After the reaction was complete, the solid product was obtained by filtration, washed thoroughly with deionized water, and dried under vacuum at 80 °C for 24 h to obtain the final product.
[0042] Preparation Example 3 This preparation example provides a method for preparing a vanadate-polyaniline composite, comprising the following steps: Aniline (0.93 g) was dissolved in 50 mL of 0.3 mol / L sulfuric acid aqueous solution and stirred until homogeneous to obtain solution A; ammonium vanadate hexahydrate (NH4)6V 10 O 28 ·6H₂O (1.86 g) and sodium persulfate (4.65 g) were dissolved in deionized water (50 mL), and the pH was adjusted to 2-3 with dilute sulfuric acid (0.1 mol / L). The mixture was stirred until completely dissolved to obtain solution B. Under stirring conditions at room temperature (25 °C), solution A was added dropwise to solution B at a rate of 3-5 s / drop. After the addition was complete, the reaction was continued with stirring for 30 h. After the reaction was complete, the solid product was obtained by filtration, washed thoroughly with deionized water, and dried under vacuum at 80 °C for 24 h to obtain the final product.
[0043] Example 1 This embodiment provides a method for preparing a negative electrode sheet, including the following steps: (1) At room temperature, lithium difluorosulfonyl imide, polyethylene glycol diacrylate (number average molecular weight of 4000), 2,2,2,-trifluoroethyl acrylate, maleic acid and azobisisobutyronitrile were dissolved in ethanol to obtain a mixed solution; wherein, the mass ratio of polyethylene glycol diacrylate to 2,2,2,-trifluoroethyl acrylate was 1:2, the molar ratio of 2,2,2,-trifluoroethyl acrylate to maleic acid was 1:1.5, the mass of azobisisobutyronitrile was 1.5wt% of the total mass of polyethylene glycol diacrylate, 2,2,2,-trifluoroethyl acrylate and maleic acid, the lithium difluorosulfonyl imide was calculated as lithium element, the polyethylene glycol diacrylate was calculated as ethylene oxide segment, and the molar ratio of ethylene oxide segment to lithium element was 18:1; (2) Add the vanadate-polyaniline composite prepared in Preparation Example 1 to the above mixed solution and stir for 30 min. Then add micron-sized silicon (particle size of 5 μm) and continue stirring and dispersing for 30 min to obtain the negative electrode slurry. The mass ratio of the total mass of the micron-sized silicon material to polyethylene glycol diacrylate, 2,2,2-trifluoroethyl acrylate and maleic acid and the vanadate-polyaniline composite is 8:1:1. The amount of ethanol used is based on the total mass of the remaining solids after deducting the lithium difluorosulfonyl imide salt. The solid content of the negative electrode slurry is 25 wt%. (3) The above slurry is uniformly coated on the copper current collector, and then heated at 70°C for 10 hours in an inert atmosphere, and then heated to 90°C for 10 hours to obtain the negative electrode sheet.
[0044] Example 2 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the vanadate-polyaniline composite prepared in Example 1 is replaced with the same mass of the vanadate-polyaniline composite prepared in Example 2.
[0045] Example 3 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the vanadate-polyaniline composite prepared in Example 1 is replaced with the same mass of the vanadate-polyaniline composite prepared in Example 3.
[0046] Example 4 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the mass ratio of polyethylene glycol diacrylate to 2,2,2-trifluoroethyl acrylate is 1:1.
[0047] Example 5 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the mass ratio of polyethylene glycol diacrylate to 2,2,2-trifluoroethyl acrylate is 1:3.
[0048] Example 6 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the molar ratio of 2,2,2,-trifluoroethyl acrylate and maleic acid is 1:0.5.
[0049] Example 7 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the molar ratio of 2,2,2-trifluoroethyl acrylate and maleic acid is 1:3.
[0050] Example 8 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Embodiment 1, except that the lithium bis(fluorosulfonyl)imide salt is calculated as lithium element, the polyethylene glycol diacrylate is calculated as ethylene oxide segments, and the molar ratio of ethylene oxide segments to the lithium element is 16:1.
[0051] Example 9 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Embodiment 1, except that the lithium bis(fluorosulfonyl)imide salt is calculated as lithium element, the polyethylene glycol diacrylate is calculated as ethylene oxide segments, and the molar ratio of ethylene oxide segments to the lithium element is 20:1.
[0052] Example 10 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the mass ratio of the total mass of the micron-sized silicon material, polyethylene glycol diacrylate, 2,2,2-trifluoroethyl acrylate and maleic acid to the mass ratio of the vanadate-polyaniline composite is 8:0.5:1.5.
[0053] Example 11 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the mass ratio of the total mass of the micron-sized silicon material, polyethylene glycol diacrylate, 2,2,2-trifluoroethyl acrylate and maleic acid to the mass ratio of the vanadate-polyaniline composite is 8:1.5:0.5.
[0054] Example 12 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that polyethylene glycol diacrylate is replaced with polyethylene glycol dimethacrylate with the same number average molecular weight.
[0055] Example 13 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that 2,2,2-trifluoroethyl acrylate is replaced with 2,2,2-trifluoroethyl methacrylate.
[0056] Example 14 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that 2,2,2-trifluoroethyl acrylate is replaced with 2,2,3,3-tetrafluoropropyl methacrylate.
[0057] Example 15 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that 2,2,2-trifluoroethyl acrylate is replaced with 1,1,1,3,3,3-hexafluoroisopropyl acrylate.
[0058] Example 16 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Embodiment 1, except that maleic acid is replaced with the same mass of citralic acid.
[0059] Example 17 This embodiment provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Embodiment 1, except that maleic acid is replaced with itaconic acid.
[0060] Comparative Example 1 This comparative example provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that polyethylene glycol diacrylate is replaced with the same mass of 2,2,2,-trifluoroethyl acrylate, and the amount of lithium difluorosulfonyl imide added remains unchanged, which is exactly the same as the mass of lithium salt in Example 1.
[0061] Comparative Example 2 This comparative example provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that 2,2,2,-trifluoroethyl acrylate is replaced with the same mass of polyethylene glycol diacrylate, and the molar ratio of ethylene oxide segments to lithium elements is maintained at 18:1.
[0062] Comparative Example 3 This comparative example provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that maleic acid is replaced with the same number of moles of 2,2,2-trifluoroethyl acrylate.
[0063] Comparative Example 4 This comparative example provides a method for preparing a negative electrode sheet, which is basically the same as the steps in Example 1, except that the vanadate-polyaniline composite is replaced with the same mass of polyethylene glycol diacrylate.
[0064] Comparative Example 5 This comparative example provides a method for preparing a negative electrode sheet, including the following steps: Micron-sized silicon, polyacrylic acid (PAA), and conductive carbon black (SP) were dispersed in water at a mass ratio of 8:1:1 to obtain a negative electrode slurry with a solid content of 25wt%. This slurry was coated onto copper foil and dried to obtain a negative electrode sheet.
[0065] Experimental Example Lithium chloride-sulfur-phosphorus (LPSCI) electrolyte with a median particle size of 3 μm was placed in a 70 MPa mold and pressed for 3 min to obtain an LPSCI electrolyte membrane with a thickness of 0.7 mm. Then, the negative electrode sheets prepared in Examples 1-17 and Comparative Examples 1-5 were placed on one side of the electrolyte membrane, and a Li-In alloy sheet was placed on the other side. After pressing at 370 MPa for 10 min, a long-cycle test was performed (test procedure: voltage window -0.62~0.88V vs Li-In, test current 0.1C, 1C=3500mA / g). CE was calculated as the average coulombic efficiency after 3 cycles of stabilization. Before EIS and rate testing, the battery was cycled 3 times at 0.1C. Then, the contact impedance and bulk resistance were tested by EIS at a frequency of 0.01-100000Hz. A rate test was then performed at 1.5C. All batteries were tested while maintaining a pressure of 10 MPa. The test results are shown in Table 1. The cycle test results of the sulfide all-solid-state half-cell obtained in Example 1 are shown in Table 1. Figure 2 As shown, the battery impedance after 50 cycles is shown in the figure. Figure 3 As shown. Peel strength test method: The electrode to be tested is fixed to a rigid substrate with double-sided tape or directly. A tensile testing machine is used to peel the electrode from the substrate in a 180° direction. The electrode peel strength is shown in [the figure]. Figure 4 As shown.
[0066] Table 1. Battery performance test results obtained from each embodiment and comparative example.
[0067] From Table 1 and Figures 2-4It can be seen that the all-solid-state sulfide batteries prepared in Examples 1-17 of this invention can operate under low external pressure (10MPa), and the electrode peel strength can reach 10N / cm. Due to the formation of a stable interface layer, the first-cycle efficiency of the half-cell can reach 75%-82.8%, and the CE is 99.38%-99.96% in subsequent cycles. After the first cycle, the battery impedance is lower, with a bulk resistance of 20Ω-42Ω and a contact impedance of 22Ω-61Ω, and the impedance increases slowly during cycling. The battery retains more than 72% of its capacity after 50 cycles. In addition, the all-solid-state sulfide half-cell can maintain a capacity of 1990-2340mAh / g at 0.1C. In contrast, Comparative Example 1 omitted the addition of polyethylene glycol diacrylate, resulting in a linear polymer, which is not a three-dimensional network structure. This leads to a lack of effective elastic network, which cannot limit the volume expansion of silicon. Cracks and pores are easily formed inside the electrode, and stable ions cannot be formed. The permeation network leads to increased impedance; Comparative Example 2 omits the addition of 2,2,2,-trifluoroethyl acrylate, failing to form a LiF-rich SEI, resulting in continuous decomposition of sulfide electrolyte at the interface, leading to decreased battery initial efficiency and increased contact impedance; Comparative Example 3 omits the addition of maleic acid, lacking the ability to form hydrogen bonds and covalent bonds between -COOH and -OH on the silicon surface, failing to anchor silicon particles and restrict silicon volume expansion, making the electrode internally prone to cracking and the interface prone to peeling, resulting in increased battery impedance and a sharp decline in cycle life; Comparative Example 4 only has a three-dimensional multifunctional binder network, lacking an effective conductive network, leading to a sharp increase in impedance and accelerated capacity decay during battery cycling; Comparative Example 5 uses a traditional negative electrode preparation method, which cannot effectively avoid the continuous decomposition of sulfides and lacks three-dimensional polymer constraints and an effective ion / electron permeation network, resulting in severe internal cracking of the electrode, which in turn restricts ion / electron transport within the electrode and drastically deteriorates electrical performance.
[0068] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A negative electrode sheet, characterized in that, The present invention includes a current collector and a negative electrode slurry coated on at least one side of the current collector, wherein the raw materials of the negative electrode slurry include: silicon active material, lithium salt, initiator, crosslinking agent, stabilizing functional monomer, adhesion functional monomer and vanadate-polyaniline composite. The crosslinking agent contains an oxyethylene segment and two substituted or unsubstituted acryloyl groups; wherein the substituents of the substituted acryloyl groups include C1-C3 alkyl groups; The stabilizing functional monomer contains acrylates with 3-6 fluorine atoms substituted for alkyl groups; The adhesive functional monomer contains double bonds and carboxyl groups; The crosslinking agent includes at least one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate; The number average molecular weight of the polyethylene glycol diacrylate is 3000-5000; The number-average molecular weight of the polyethylene glycol dimethacrylate is 3000-5000; The adhesive functional monomer includes at least one of maleic acid, itaconic acid, citraconic acid, and acrylic acid.
2. The negative electrode sheet according to claim 1, characterized in that, The stabilizing functional monomers include at least one of 2,2,2-trifluoroethyl acrylate, 2,2,2-trifluoroethyl methacrylate, hexafluorobutyl acrylate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, and 1,1,1,3,3,3-hexafluoroisopropyl acrylate.
3. The negative electrode sheet according to claim 1 or 2, characterized in that, The mass ratio of the crosslinking agent to the stable functional monomer is 1:(1-3). And / or, the molar ratio of the stabilizing functional monomer to the adhesive functional monomer is 1:(0.5-3). And / or, the mass of the initiator is 1wt%-2wt% of the total mass of the crosslinking agent, the stabilizing functional monomer, and the adhesion functional monomer; And / or, the lithium salt is calculated as elemental lithium, the crosslinking agent is calculated as ethylene oxide segments, and the molar ratio of the ethylene oxide segments to the elemental lithium is (16-20):1; And / or, the total mass ratio of the crosslinking agent, the stabilizing functional monomer and the adhesion functional monomer to the mass ratio of the silicon active material and the vanadate-polyaniline composite is (0.5-1.5):8:(0.5-1.5).
4. The negative electrode sheet according to claim 1, characterized in that, The preparation method of the vanadate-polyaniline composite includes the following steps: aniline reacts with sulfuric acid solution to obtain mixed solution A; ammonium decavanadate and oxidant react in deionized water to obtain mixed solution B; mixed solution A reacts with mixed solution B to obtain vanadate-polyaniline composite; the pH value of mixed solution B is 2-3.
5. The negative electrode sheet according to claim 4, characterized in that, The molar ratio of aniline to sulfuric acid is 1:(0.5-1.5). And / or, the oxidant includes at least one of ammonium persulfate, potassium persulfate, and sodium persulfate; And / or, the mass ratio of the aniline, the ammonium decavanadate, and the oxidant is 1:(0.5-2):(2-5); And / or, the reaction temperature is room temperature and the reaction time is 18h-30h.
6. The negative electrode sheet according to claim 1, characterized in that, The lithium salt includes at least one of bis(trifluoromethane)sulfonylimide lithium salt and bis(trifluoromethane)sulfonylimide lithium salt; And / or, the initiator includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile; And / or, the silicon active material includes at least one of micron-sized silicon, silicon-oxygen materials, and silicon-carbon materials.
7. The negative electrode sheet according to claim 6, characterized in that, The particle size of the micron-sized silicon is 1μm-5μm.
8. A method for preparing a negative electrode sheet as described in any one of claims 1-7, characterized in that, The process includes the following steps: mixing the raw materials of the negative electrode slurry, reacting to obtain the negative electrode slurry, coating it onto the current collector, and then heating it to obtain the final product.
9. The method for preparing the negative electrode sheet according to claim 8, characterized in that, The heating steps include: first heating at 60℃-80℃ for 5h-15h, and then heating at 85℃-95℃ for 5h-15h; And / or, the heating step is performed under an inert atmosphere or a vacuum.
10. The application of a negative electrode sheet prepared by the method of any one of claims 1-7 or claim 8 or 9 in a solid-state lithium-ion battery.
Citation Information
Patent Citations
Fluorine-containing polymer binder, and preparation method and application thereof in silicon-based electrode lithium ion battery
CN109880017A
Positive pole piece, solid-state battery containing positive pole piece and preparation method of positive pole piece
CN118522979A